A comparative study of processed Moringa leaves and Fe tablet supplementation on hemoglobin levels among mildly anemic pregnant women - Sari Narulita; Royani Chairiyah (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Anemia is a condition characterized by hemoglobin (Hb) levels below normal physiological values based on age and sex. Among pregnant women, anemia poses serious health risks to both the mother and the fetus, including miscarriage, preterm birth, infection, hemorrhage, intrauterine fetal death, low birth weight, congenital anomalies, perinatal mortality, and reduced infant intelligence. In Bekasi City, the prevalence of anemia among pregnant women increased from 14.3% in 2021 to 20% in 2022, largely due to poor adherence to iron (Fe) tablet supplementation, often caused by side effects such as nausea and unpleasant taste. Purpose: To compare the effectiveness of processed Moringa leaves (Moringa oleifera) and Fe tablets in improving hemoglobin levels among pregnant women with mild anemia. Method: A quantitative experimental design with a two-group pretest–posttest approach was used. The study was conducted at Mrs. Ida Roningsih’s Independent Midwife Practice from August 1 to September 31, 2024, involving all pregnant women in the working area, totaling 44 participants. Data were collected through hemoglobin measurements before and after intervention and questionnaire responses. Statistical analyses included univariate and bivariate analysis, the Shapiro–Wilk normality test, and T-test or Wilcoxon test as appropriate. Results: The mean increase in hemoglobin levels among pregnant women in the Moringa leaf group was 1.35 g/dL (6.15%), compared to only 0.09 g/dL (0.4%) in the Fe tablet group. A significant difference was observed between the intervention and control groups (p = 0.000). The relative risk (RR) of 2.375 indicates that pregnant women receiving Moringa leaf capsules were 2.375 times more likely to experience an increase in Hb levels compared to those taking Fe tablets. Conclusion: Processed Moringa leaves (Moringa oleifera) were proven to be more effective than Fe tablets in increasing hemoglobin levels among pregnant women with mild anemia, showing a more than twofold greater improvement in Hb levels.